Ultrarare Variants in DNA Damage Repair Genes in Pediatric Acute-Onset Neuropsychiatric Syndrome or Acute Behavioral Regression in Neurodevelopmental Disorders - Cunningham, Janet L.; Frankovich, Jennifer; Dubin, Robert A.; Pedrosa, Erika; Baykara, Refia Nur; Schlenk, Noelle Cathleen; Maqbool, Shahina B.; Dolstra, Hedwig; Marino, Jacqueline; Edinger, Jacob; Shea, Julia M.; Laje, Gonzalo; et al. (Developmental neuroscience, 2025)
AbstractIntroduction: Acute onset of severe psychiatric symptoms or regression may occur in children with premorbid neurodevelopmental disorders, although typically developing children can also be affected. Infections or other stressors are likely triggers. The underlying causes are unclear, but a current hypothesis suggests the convergence of genes that influence neuronal and immunological function. We previously identified 11 genes in pediatric acute-onset neuropsychiatric syndrome (PANS), in which two classes of genes related to either synaptic function or the immune system were found. Among the latter, three affect the DNA damage response (DDR): PPM1D, CHK2, and RAG1. We now report an additional 17 cases with mutations in PPM1D and other DDR genes in patients with acute onset of psychiatric symptoms and/or regression that their clinicians classified as PANS or another inflammatory brain condition. Methods: We analyzed genetic findings obtained from parents and carried out whole-exome sequencing on a total of 17 cases, which included 3 sibling pairs and a family with 4 affected children. Results: The DDR genes include clusters affecting p53 DNA repair (PPM1D, ATM, ATR, 53BP1, and RMRP), and the Fanconi Anemia Complex (FANCE, SLX4/FANCP, FANCA, FANCI, and FANCC). We hypothesize that defects in DNA repair genes, in the context of infection or other stressors, could contribute to decompensated states through an increase in genomic instability with a concomitant accumulation of cytosolic DNA in immune cells triggering DNA sensors, such as cGAS-STING and AIM2 inflammasomes, as well as central deficits on neuroplasticity. In addition, increased senescence and defective apoptosis affecting immunological responses could be playing a role. Conclusion: These compelling preliminary findings motivate further genetic and functional characterization as the downstream impact of DDR deficits may point to novel treatment strategies.